Karakteristik Soldering Baja Perkakas H13 Modifikasi Setelah Kombinasi Proses Shot Peening Dan Nitriding - Aditya Herliawan (Jurnal Optimasi Teknik Industri (JOTI), 2019)
Failure Soldering characteristic on die casting makes it’s should be had high wear ability erosion and also released from white layer embrittlement on nitriding process. Both of shot peening and nitriding are kind of process which can increasing surface strength characterization in structural or mechanical components and also as an affricative way to prevent soldering. This research has spesific purpose how to learn affected morphology of layer, surface, and hardness on H13 modification after shot peening & nitriding. In this case research, H13 tool steel will be compared with superior which each part of material has 5 combination surface treatment and 2 kind of holding time of nitriding. Then dipped into the molten of ADC12 Aluminum at temperature 680oC and held for 30 second, 5 minutes and 30 minutes. Characterizations on the surface of the steel were focused on the microstructure, microhardness profile, surface roughness, and weight loss of the H13 tool steel. Result found that H13 modification show hardness until 1415,9 HV compare with only shot peening treatment. This research result showed that best resistance to soldering to create from combination shot peening before and after nitriding.Keywords: Process Design, Knowledge Management, Innovation Strategy